2021
DOI: 10.1002/joc.6949
|View full text |Cite
|
Sign up to set email alerts
|

A climatological analysis of the monsoon break following the summer monsoon onset over Luzon Island, Philippines

Abstract: This study investigates the climatology of the monsoon break following the onset of the summer rainy season over Luzon Island (120−122.5° E, 13−22° N) in the Philippines from 1979−2017. The first post-onset monsoon break is remarkable in stations located over the north and central Luzon Island and occurs climatologically in early June. Composite analysis of the large-scale circulation features during the monsoon break period shows that this break is associated with the westward extension of the western North P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 52 publications
6
18
0
Order By: Relevance
“…We also examined the June-July 2007 dry spell over Luzon region and found that the days with low rainfall amounts coincided with the suppressed BSISO phases (Phases 1-4) over the western North Pacific. This result corroborates the results found by Olaguera et al (2021) who demonstrated that the majority of the post onset monsoon break cases over the Luzon region occur during the suppressed phases of the BSISO over the western North Pacific.…”
Section: Summary and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We also examined the June-July 2007 dry spell over Luzon region and found that the days with low rainfall amounts coincided with the suppressed BSISO phases (Phases 1-4) over the western North Pacific. This result corroborates the results found by Olaguera et al (2021) who demonstrated that the majority of the post onset monsoon break cases over the Luzon region occur during the suppressed phases of the BSISO over the western North Pacific.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…Figure 7a shows the BSISO phase-space diagram from June 1, 2007 to August 31, 2007, while Figure 7b shows the average daily rainfall from the eight PAGASA stations (Laoag, Vigan, Dagupan, Iba, Science Garden Ambulong, Coron, and Baguio stations) located on the western coast of the Luzon region. These stations are similar to those used by Cruz et al (2013) and Olaguera et al (2021) in characterizing the southwest monsoon season of the Philippines. From June 1-24, the active convection of the BSISO is located over the Bay of Bengal and convection is suppressed over the western North Pacific.…”
Section: Relationship Between Bsiso and The June-july 2007 Dry Spell ...supporting
confidence: 53%
See 2 more Smart Citations
“…The western part of the Philippines and coastal waters to its west are a region in the Asian monsoon domain with heavy precipitation in boreal summer (Matsumoto et al., 2020; Shige et al., 2017; Xie et al., 2006), primarily caused by horizontal convergence and uplift of lower‐tropospheric southwesterly monsoon winds due to topography. Precipitation variability in this region is caused by various atmospheric disturbances, such as typhoons (Bagtasa, 2017, 2019; Cayanan et al., 2011), quasi‐biweekly oscillations (QBWOs; Natoli & Maloney, 2021), and boreal summer intraseasonal oscillations (BSISOs; Bagtasa, 2020; Ho et al., 2008; Natoli & Maloney, 2019; Olaguera et al., 2021). Furthermore, the diurnal cycle is conspicuous (Hilario et al., 2021; Natoli & Maloney, 2019), as in other tropical coastal areas (Kikuchi & Wang, 2008; Yang & Slingo, 2001).…”
Section: Introductionmentioning
confidence: 99%